STRUCTURAL BASIS OF INCREASED BONE FRAGILITY IN ELDERLY INDIVIDUALS : MULTI-SCALE PERSPECTIVE: AGING RELATED BONE FRAGILITY DETERMINANTS - Jadzic, Jelena; Djuric, Marija (Medical Research, 2024)
Numerous epidemiological studies have shown that increased bone fragility and a higher risk of fractures are present in older individuals with various chronic diseases, which reduces the quality of life and represents a significant socio-economic burden on the health system. However, the morphological and structural determinants underlying increased bone fragility have yet to be fully explained. This paper provides an overview of modern studies that dealt with determinants of increased bone fragility, analyzing different hierarchical levels of bone tissue organization (macro-, micro-, and nano-levels) in aged individuals with chronic diseases. Also, a variable frequency of fractures at different skeletal sites in elderly persons with chronic diseases was shown, indicating that aging-related bone loss is not a uniform process. A complete understanding of the spatial pattern of impaired bone quality can aid in the targeted evaluation of individualized fracture risk. Establishing a connection between the results of the clinical assessment of bone status and the analysis of numerous structural and mechanical bone properties can represent a solid base for developing timely methods of prevention and treatment of increased bone fragility in aged individuals with chronic diseases.